KEANEKARAGAMAN JENIS TUMBUHAN PENCEGAH EROSI DI DAERAH ALIRAN SUNGAI (DAS) CILIWUNG - Sri Wiedarti; Herdi Ramdan; Cecep Sudrajat (EKOLOGIA, 2014)
The study was conducted at two locations, namely the headwaters and mid stream part Ciliwung. A teach location made six transects with 45m length of each transect. Each transect made 5 sample plots measuring 1x1m with the distance between sample plots is 10m. Then be identified, then calculated FR, KR, INP and Diversity Index Type. Based on the research results, There are 23 species of plants preventing erosion which is included in the 14 family. Ciliwung headwaters part there are 19 species of plants preventing erosion of the 12 family, with a percentage of 57,5% and the highest Importance Value Index was Panicum maximum of 41.83%. Ciliwung midstream part there are 15 species of plants preventing erosion of the 9 tribes, with a percentage 45,4% and the highest Importance Value Index was Pennisetum purpureum of 44.16%. Plant species diversity index prevention of erosion in watersheds (DAS) Ciliwung low with values ranging between 0,90-0,95.Key words: erosion control plants, watershed (DAS), Ciliwung